Penerapan Strategi Ekspositori pada Pembelajaran Dendang di Kelas XI Karawitan SMK Negeri 7 Padang - Febi Nurdiana; Irdhan Epria Darma Putra (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
This research aims to describe the application of expository strategy in learning dendang in class XI Karawitan SMK N 7 Padang. This type of research is qualitative research with descriptive method. The instrument of this research is the researcher himself and assisted by supporting instruments such as stationery and camera. Data were collected through observation, literature study, interviews and documentation. The steps of analyzing data are collecting data, classifying data, reclassifying data and concluding data. This expository strategy is implemented with 5 stages, namely the preparation stage, presentation stage, connecting stage, concluding stage, applying stage. In the preparation stage, the teacher prepares lesson plans in accordance with the learning outcomes. The presentation stage, the teacher provides learning material. The connecting stage, the teacher connects the learning material with the students' experience. The stage of concluding, the teacher concludes the learning outcomes to students at the end of the lesson. Stages of applying, namely students applying or practicing learning material in front of the class.